Communication in Eighteenth-Century Music - Mirka, Danuta; Agawu, Kofi (Cambridge Cambridge University Press, 2008)
Written by ten leading scholars, this 2008 volume assembles studies of eighteenth- and early nineteenth-century music under the broad rubric of communication. That such an impulse motivates musical composition and performance in this period of European musical history is often acknowledged but seldom examined in depth. The book explores a broad set of issues, ranging from the exigencies of the market for books and music in the eighteenth century through to the deployment of dance topoi in musical composition. A number of close readings of individual works by Mozart, Haydn and Beethoven draw on a sophisticated body of historically-appropriate technical resources to illuminate theories of form, metre, bass lines and dance topoi. Students and scholars of music history, theory and analysis will find in this volume a set of challenging, state-of-the-art essays that will stimulate debate about musical meaning and engender further study.
Keywords: Performance